Chronic Human Infection with Trypanosoma cruzi Drives CD4(+) T Cells to Immune Senescence - Albareda, María Cecilia (2009)
Previously we found that the frequency of IFN-γ-producing CD8(+) T cells specific for Trypanosoma cruzi inversely correlates with disease severity in chronic human Chagas disease along with low levels of IL-2-secreting CD8(+) T cells in all clinical stages. This impairment of the parasite-specific T cell responses was associated with phenotypic features of immune senescence of the CD8(+) T cell compartment. These data prompted us to address the question of whether the CD4(+) T cell compartment also experiences signs of exhaustion. Thus, we performed a functional and phenotypical characterization of T. cruzi-specific and overall CD4(+) T cells in chronically infected subjects with different degrees of cardiac dysfunction. The results show an inverse association between disease severity and the frequency of T. cruzi-specific IFN-γ-producing CD4(+) T cells. The high expression of CD27 and CD28 with a relative low expression of CD57 found on CD4(+)IFN-γ (+) T cells suggests that the effector T cell pool in chronic T. cruzi infection includes a high proportion of newly recruited T cells, but a low frequency of long-term memory cells. The total CD4(+) T cell compartment shows signs of senescence and later stages of differentiation associated with more severe stages of the disease. These findings support the hypothesis that long-term T. cruzi infection in humans might exhaust long-lived memory T cells.